Reactivity ratio determination of newly synthesized copolymers from glycidyl methacrylate and tetrahydrofurfuryl acrylate - Ahmad Danial Azzahari,; Rosiyah Yahya,; Aziz Hassan, (Universiti Kebangsaan Malaysia, 2013)
Copolymers from different feed compositions of glycidyl methacrylate (GMA) and tetrahydrofurfuryl acrylate (THFA) were synthesized using free radical polymerization in toluene solution at 70±1°C using benzoyl peroxide (BPO) as initiator. The polymers were characterized by 1H NMR,13C NMR and DEPT spectroscopic techniques. The copolymer compositions were determined using 1H NMR analysis. Reactivity ratios for GMA and THFA were determined by the Kelen-Tudos, Tidwell-Mortimer and error-in-variables model methods. The results showed that all these copolymerizations were strictly linear systems describable by the Mayo-Lewis equation based on the terminal model and that accurate reactivity ratio data can be obtained.